Quelle prévention des TMS dans l’activité de l’encadrement de proximité en sous-traitance interne ? Un cas dans le secteur de la découpe de viande - Aude Cuny-Guerrier; Sandrine Caroly; Fabien Coutarel; Agnès Aublet-Cuvelier (Perspectives Interdisciplinaires sur le Travail et la Santé)
The goal of this paper is to document through a case study how a first-line, subcontracted foreman in the meat-cutting sector contributed to the creation of favorable working arrangements for MSD prevention in butchers. Data collection focused on the foreman’s regulation activities and their determinants. The methodology involved interviews, observations, and self-analyses. Our results suggest that the first-line foreman succeeded, in a context of work constraints and regulations, in loosening up some of the organizational constraints for the butchers. These regulations concerned the management of human resources and the foreman’s participation in production activities. In this sub-contracting context, these regulations focused primarily on greater performance and, at a first glance, only indirectly on the health preservation of the butchers.